Clinical Significance of Horizontal and Vertical Margin of En Bloc Resection for Nonmuscle Invasive Bladder Cancer. Issue 2 (29th August 2021) - Yanagisawa, Takafumi; Miki, Jun; Sakanaka, Keigo; Fukuokaya, Wataru; Iwatani, Kosuke; Sato, Shun; Obayashi, Koki; Hirooka, Shinichi; Kimura, Takahiro; Takahashi, Hiroyuki; Egawa, Shin
Abstract : Purpose: The primary advantage of en bloc resection of bladder tumors is to provide better diagnostic accuracy. However, the clinical significance of horizontal and vertical margin has not been demonstrated. We evaluated the clinical importance of surgical margins in patients who underwent en bloc resection of bladder tumors. Materials and Methods: We retrospectively analyzed the records of 140 consecutive patients who underwent en bloc resection of bladder tumors for nonmuscle invasive bladder cancer. We analyzed perioperative and oncological outcome, and compared patient demographics and recurrence-free survival for horizontal findings. The relationship between surgical margin and second transurethral resection outcome in pT1 bladder cancer was also analyzed. Results: Mean tumor diameter was 17.2±9.8 mm. Pathological stages were 93 cases in pTa and 47 cases in pT1. Diagnostic rates for the horizontal and vertical margins were 63% and 99%, respectively. The rates of sessile, carcinoma in situ, high grade, and pT1 tumors were significantly higher in the horizontal margin positive group (41) than in the negative group (47). There was no significant difference in 2-year recurrence-free survival based on horizontal margin findings (negative: 72.4%, positive: 75.4%, p=0.87). A second transurethral resection was performed in 31 of the 47 pT1 patients; pT1 residue was seen only in vertical margin positive cases, and 5 pTa/pTis residues at the transurethral resection scar were seen in 15 horizontal margin positive patients. Conclusions: Horizontal margin positive findings were not associated with recurrence-free survival, but careful assessment is warranted regarding residue at the original site. A second transurethral resection should be considered in patients with horizontal and vertical margin positive pT1 bladder cancer.